(untitled) (Third Sector Social Economic Review, 2024)
The 2008 global financial crisis, which started in the US real estate market and gained global character, is considered the most severe financial crisis after the Great Depression. The crisis, which had economic and social consequences all over the world, also affected the Japanese economy with its deep and interconnected financial system. The US Federal Reserve (Fed) and the Bank of Japan (BoJ) intervened in the crisis with a policy set that included unconventional monetary policy. Covid-19, which turned into an epidemic in 2020, also affected the financial sector by causing disruptions in supply and demand channels. The Fed and the BoJ changed the scope of some of the policy options used during the global financial crisis and implemented them. This study examined financial crisis models, focusing on the causes of the 2008 global financial crisis and its similarities and differences with previous crises. It was found that the crisis was not solely due to mortgage loans, but also to practices in the financial sector, including asymmetric information, adverse selection, and moral hazard. The monetary policies of the Fed and BoJ were analyzed, revealing variations in instruments, scope, and timing due to differences in financial markets.